2005
DOI: 10.1104/pp.105.066134
|View full text |Cite
|
Sign up to set email alerts
|

Sorghum Expressed Sequence Tags Identify Signature Genes for Drought, Pathogenesis, and Skotomorphogenesis from a Milestone Set of 16,801 Unique Transcripts

Abstract: Improved knowledge of the sorghum transcriptome will enhance basic understanding of how plants respond to stresses and serve as a source of genes of value to agriculture. Toward this goal, Sorghum bicolor L. Moench cDNA libraries were prepared from light-and dark-grown seedlings, drought-stressed plants, Colletotrichum-infected seedlings and plants, ovaries, embryos, and immature panicles. Other libraries were prepared with meristems from Sorghum propinquum (Kunth) Hitchc. that had been photoperiodically induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 54 publications
(69 reference statements)
4
33
0
Order By: Relevance
“…For example, 178,000 cDNAs (ESTs) that were randomly sequenced from 61 different cDNA libraries made from different tissues, biotic-and abioticstress challenged and different developmental stages of Arabidopsis identified only 16,115 distinct genes (see Rudd 2003). Similar results were observed in maize (Fernandes et al 2002), sorghum (Pratt et al 2005) and wheat (Houde et al 2006).…”
Section: Introductionsupporting
confidence: 60%
“…For example, 178,000 cDNAs (ESTs) that were randomly sequenced from 61 different cDNA libraries made from different tissues, biotic-and abioticstress challenged and different developmental stages of Arabidopsis identified only 16,115 distinct genes (see Rudd 2003). Similar results were observed in maize (Fernandes et al 2002), sorghum (Pratt et al 2005) and wheat (Houde et al 2006).…”
Section: Introductionsupporting
confidence: 60%
“…The authors estimated that their unigene set might have covered upwards of 67% of the grape transcriptome, assuming that the grapevine genome contains ∼ 38,000 genes (da Silva et al, 2005); however, this number of unique sequences derived via computational clustering and assembly of ESTs likely represents an overestimate of the grape genes identified, since the ESTs analyzed represent cDNAs sequenced from both 5′ and 3′ ends. A higher false positive (and false negative) rate was previously observed with 5′ EST clustering (Pratt et al, 2005;Park et al, 2006). For example, using the information available for the Arabidopsis genome, Wang et al (2004) demonstrated that the rate of incorrectly separating ESTs from the same gene into two or more clusters is 30% with 5′ ESTs and 3% with 3′ ESTs.…”
Section: Introductionmentioning
confidence: 76%
“…In the present study, we obtained unamplified titers of 1.28 x 10 6 pfu/mL and 1.70 x 10 10 pfu/mL, and inserts between 100 and 1100; 91.2% of the recombinant cDNA library indicated that good quality can provide a basis for the in-depth study of the transcriptional levels of athletes. Another study demonstrated expressed sequence tags (EST) analysis for the study of functional genomics in terms of nucleotide sequences greater than 300 bp that represent information (Pratt et al, 2005). A total of 406 clones were sequenced after the removal of randomly selected sequences of less than 300 bp, leaving 360 sequences of lengths ranging from 300 to 1100, with an average length of 606 bp, which further indicates that the library was well constructed.…”
Section: Discussionmentioning
confidence: 99%